The effect of high-intensity intermittent and moderate-intensity continuous exercises on neurobiological markers and cognitive performance - Buzdagli, Y.; Ozan, M.; Baygutalp, N.; Oget, F.; Karayigit, R.; Yuce, N.; Kan, E.; Baygutalp, F.; Ucar, H.; Buzdagli, Y. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background The effects of exercise on cognitive functions and general brain health have been increasingly studied. Such studies conducted among athletes are very important to understanding the effects of different exercise methods on biochemical parameters and cognitive performance. The present study aimed to compare the neuroprotective effects of high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) based on biochemical parameters and cognitive performance in athletes.